2016
DOI: 10.17219/acem/28820
|View full text |Cite
|
Sign up to set email alerts
|

Mastalgia Due to Degenerative Changes of the Spine

Abstract: people, and the prevalence increases in the fifth decade of life. Cervical radiculopathy is the result of cervical nerve root pathology, often caused by space-occupying lesions such as cervical disc herniation, spondylosis, or osteophytosis. These space-occupying lesions produce upper extremity radicular symptoms such as pain, numbness, weakness and paresthesia. The C6 and C7 nerve roots are most commonly involved in cervical radiculopathy [3].The aim of the present study was to define the incidence of vertebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…None were randomized controlled trials (RCTs) and five were case studies [ 11 , 12 , 14 - 16 ]. The remaining two were a prospective cohort study and a retrospective cohort study [ 3 , 13 ]. Patient characteristics are described below in the meta-narrative of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…None were randomized controlled trials (RCTs) and five were case studies [ 11 , 12 , 14 - 16 ]. The remaining two were a prospective cohort study and a retrospective cohort study [ 3 , 13 ]. Patient characteristics are described below in the meta-narrative of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The overall study quality assessment demonstrated three studies had “good” quality [ 12 , 14 , 16 ], one had “fair” quality [ 11 ], and three had “poor” quality of evidence [ 3 , 13 , 15 ] using the NHLBI Study Quality Assessment Tool for Observational Studies ( Figs. 2 - 4 ) [ 8 , 9 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of pain is not associated with malignancy [8]. Benign causes of breast pain are numerous and include hormonal variations, larger cup size, ill-fitting or unsupportive bra, lower levels of fitness or activity, fibromyalgia, cysts, periductal mastitis, stretching of Cooper ligaments, fat necrosis, surgery, Mondor disease, diabetic mastopathy, duct ectasia, musculoskeletal disease, referred nerve root pain from degenerative spinal changes, herpes zoster, heart disease, biliary pain, and peptic ulcer [3,5,[16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introduction/backgroundmentioning
confidence: 99%